2015
DOI: 10.1016/j.tcb.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Organelle targeting during bacterial infection: insights from Listeria

Abstract: Listeria monocytogenes, a facultative intracellular bacterium responsible for severe foodborne infections, is now recognized as a multifaceted model in infection biology. Comprehensive studies of the molecular and cellular basis of the infection have unraveled how the bacterium crosses the intestinal and feto-placental barriers, invades several cell types in which it multiplies and moves, and spreads from cell to cell. Interestingly, although Listeria does not actively invade host cell organelles, it can inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 100 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…Many bacterial pathogens have evolved the ability to interfere with host cell organelles (Escoll, Mondino, Rolando, & Buchrieser, 2016;Lebreton et al, 2015). Important cellular functions are compartmentalized in these organelles, such as DNA maintenance and gene expression in the nucleus, sorting of newly synthetized proteins and lipids in the ER and in the Golgi or bioenergetics and programmed cell death in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many bacterial pathogens have evolved the ability to interfere with host cell organelles (Escoll, Mondino, Rolando, & Buchrieser, 2016;Lebreton et al, 2015). Important cellular functions are compartmentalized in these organelles, such as DNA maintenance and gene expression in the nucleus, sorting of newly synthetized proteins and lipids in the ER and in the Golgi or bioenergetics and programmed cell death in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…At the cell level, Listeria has the ability to enter and replicate in both phagocytic and nonphagocytic cells (Cossart, ; Pizarro‐Cerda, Kuhbacher, & Cossart, ). Listeria 's intracellular life cycle involves hijacking of host‐cell pathways and interference with host cell organelles (Lebreton, Stavru, & Cossart, ). Indeed, it has been reported that Listeria alters the dynamic of mitochondria fission/fusion events (Stavru, Bouillaud, Sartori, Ricquier, & Cossart, ; Stavru, Palmer, Wang, Youle, & Cossart, ), activates the endoplasmic reticulum (ER) stress responses (Pillich, Loose, Zimmer, & Chakraborty, ), and reshapes host nuclear functions by altering histone modifications and chromatin condensation (Eskandarian et al, ; Hamon et al, ; Hamon & Cossart, ; Lebreton et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although L. monocytogenes does not invade these host cell organelles, it has developed several strategies to interfere with their functions, i.e. by inhibiting phagosomal killing and lysosomal function, by activating the ER stress response, by modulating mitochondrial dynamics, by modulating host gene expression via interference with chromatin-based regulation (for review, [83]). …”
Section: Interaction With Mitochondriamentioning
confidence: 99%
“…In Listeria infection, the secretion of listeriolysin (LLO) by Listeria decreases phagosomal calcium concentration and increases pH, which impedes phago-lysosomal fusion. The secreted effector, Lmo2459, blocks the maturation of the phagosome via the inhibition of Rab 5 [11]. Legionella containing vacuoles (LCV) inside phagocytic cells avoid fusion with lysosomes, yet the pathogen vacuole extensively communicates with the endosomal, secretory, and retrograde vesicle trafficking pathways, as well as with the endoplasmic reticulum (ER) [12].…”
Section: Introductionmentioning
confidence: 99%